Diabetes and Hearing Impairment in the United States: Audiometric Evidence from the National Health and Nutrition Examination Surveys, 1999–2004 - Bainbridge, Kathleen E. (2008)
BACKGROUND: The vasculature and neural system of the inner ear may be affected by diabetes. OBJECTIVE: To determine whether hearing impairment is more prevalent among U.S. adults with diabetes than among those without diabetes. DESIGN: Cross-sectional analysis of nationally representative data. SETTING: National Health and Nutrition Examination Survey, 1999–2004. PARTICIPANTS: 5140 non-institutionalized adults aged 20–69 years who underwent audiometric testing. MEASUREMENTS: Hearing impairment assessed from the pure tone average of thresholds over low/mid frequencies (500, 1000, 2000 Hz) and high frequencies (3000, 4000, 6000, 8000 Hz), and defined for mild or greater severity (pure tone average > 25 decibels hearing level (dB HL)) and moderate or greater severity (pure tone average > 40 dB HL). RESULTS: For low/mid frequency hearing impairment of mild or greater severity assessed in the worse ear, age-adjusted prevalence estimates (95% confidence limits) were 21.3% (15.0, 27.5) among 399 adults with diabetes and 9.4% (8.2, 10.5) among 4741 adults without diabetes. For high frequency hearing impairment of mild or greater severity assessed in the worse ear, age-adjusted prevalence estimates were 54.1% (45.9, 62.3) among those with diabetes and 32.0% (30.5, 33.5) among those without. Adjusted odds ratios (95% confidence limits) of 1.82 (1.27, 2.60) and 2.16 (1.47, 3.18) for the low/mid frequency and high frequency impairments, respectively, indicated that differences in socio-demographic characteristics, noise exposure, ototoxic medication use, and smoking did not account for the association between diabetes and hearing impairment. LIMITATIONS: Diagnosed diabetes was based on self-report and does not distinguish between type 1 and type 2 diabetes. Noise exposure assessments were based on participant recall. CONCLUSION: Adults with diabetes have a higher occurrence of hearing impairment than those without diabetes. Screening for this problem would allow for interventions to improve hearing.